Factors Influencing Domestic Tourist to Visit Bali as a Medical Tourism Destination: A Preliminary Investigation - Suci Sandi Wachyuni; Kadek Wiweka; Amarjiva Lochan; Dewi Ayu Kusumaningrum (Universitas Udayana, 2024)
The objective of this study was to examine the impact of destination image, destination image, perceived value of medical costs, and perceived value of medical facilities and services on the intention to visit Bali as a medical tourism destination. The research used quantitative methodology, employing a survey method. The population consisted of all of domestic tourists who visited Bali. The sample was 87 domestic tourists who came to Bali for medical tourism purposes. The research findings indicate that destination image, perceived value of medical costs, and perceived value of medical facilities and services have an impact on intention to visit Bali for medical tourism. However, the perception of Bali as a destination did not have any impact on tourists' intention to visit for medical tourism purposes. These findings provide both theoretical and practical implication. A collaborative effort involving several parties is necessary to enhance the branding and promotion of medical tourism.